The first dinosaurs - Burton, Jane.; Dixon, Dougal; Kirk, Steve (Illustrator) (Milwaukee : G. Stevens Pub., 1987)
Brief text and illustrations introduce the characteristics and natural environment of thirteen early dinosaurs such as Saltopus and Dimetrodon. Includes a glossary of terms and miscellaneous facts about dinosaurs.
"First published ... in the United States of America, under Time exposure, by Beauford Books, New York"--P. [2]
Includes index.
Bibliography: p. 30.
Keywords: Dinosaurs -- Juvenile literature; Dinosaurs